The effect of different antimicrobial treatment regimens on the faecal shedding of ESBL-producing Escherichia coli in horses - Schoster, A.; Spijk, J.N. van; Damborg, P.; Moodley, Arshnee; Kirchgaessner, C.; Hartnack, S.; Schmitt, S. (Elsevier, 2020)
Fourth-generation cephalosporins can select for extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae in horses, but it is unknown to what extent this occurs compared to penicillin/gentamicin combination treatment. The objective was to evaluate the effect of different antimicrobial treatments on faecal shedding and diversity of ESBL-producing Escherichia coli (ESBL-EC) in horses. Upon hospital admission, 86 horses in need of antimicrobial treatment or prophylaxis were randomly allocated to receive penicillin and gentamicin (PG) or cefquinome (CEF). Untreated horses were included as controls (NOAMD, n = 33). Faecal samples from admission (T1), 3 days after admission (T2), and faecal swabs 28 days after discharge (T3) were cultured selectively. Differences in prevalence (T1, T2, T3) and counts (T1, T2) of ESBL-EC between groups and over time were analysed. On a subset of ESBL-EC isolates, antimicrobial susceptibility testing (n = 45) and whole-genome sequencing followed by SNP-analysis (n = 46) were performed. The prevalence of ESBL-EC at T1 was 12 % with no significant difference between groups. In all groups, significantly higher carriage rates were observed at T2 and T3 compared to T1. Carriage and counts of ESBL-EC at T2 were significantly higher in treated compared to untreated horses. There was no significant difference between PG and CEF at any time points. Despite a large genetic diversity, indistinguishable ESBL clones were observed in different horses over time. In conclusion, antimicrobial treatment and hospitalization increased prevalence and counts of ESBL-EC, and transmission of ESBL-EC in the hospital was suspected. These findings highlight the importance of antimicrobial stewardship and infection control practices in equine medicine.